Sleep quality in patients with Hypertension in a Peruvian hospital at 3400 meters above sea level, 2017 - Sucasaca-Rodríguez, Cristian (2020)
Introduction: Hypertension is a public health problem; sleep disturbances are conditions that predispose to hypertension and aggravate the quality of life of hypertensive patients. Objectives: To describe the characteristics of sleep quality in patients with hypertension in a national hospital in the city of Cusco-Peru, at 3400 meters above sea level (msnm). Material and Methods: A descriptive cross-sectional study was carried out with data of the patients. Results: A total of 272 hypertensive patients were studied. The average age was 65 years and the average time of the disease was 8 years. The results show that 75% of the patients had poor sleep quality and most of the patients had a sleep duration between 6 and 7 hours. All the patients presented some sleep disturbance and 94.1% did not take any medication to sleep.